DEVELOPMENT OF STUDENT WORK SHEET BASED ON CONTEXTUAL TEACHING AND LEARNING ON COLLECTED MATERIALS - Defi Susanti Duha; Defi Yanti Hulu; Leni Marlina Laia (Afore : Jurnal Pendidikan Matematika, 2023)
The purpose of this research is to develop Student Worksheets based on Contextual Teaching and Learning on set materials that are valid, practical, and effective. The type of research used in this research is research and development or (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques used are validation sheets, student response questionnaires, and student learning outcomes tests. While the data analysis technique used is qualitative and quantitative data analysis. Based on research and discussion that the validation results of material experts were 81.66% with very feasible criteria, the validation results from media experts were 80% with very feasible criteria, and the validation results from linguists were 92% with very feasible criteria. The results of the practicality test from individual trial respondents were 70.33% with interesting and practical criteria, the results of small group trial respondents were 74.33% in the very interesting and very practical category, and the results of field trial respondents were 84.07% with the category very interesting and very practical. The effectiveness results obtained an average value of 80.69% with a very high category. Researchers hope that this LKPD can be used to improve students' abilities in set material.